2010
DOI: 10.1016/j.schres.2009.09.030
|View full text |Cite
|
Sign up to set email alerts
|

Amplitude of low-frequency oscillations in schizophrenia: A resting state fMRI study

Abstract: Recently, a great deal of interest has arisen in resting state fMRI as a measure of tonic brain function in clinical populations. Most studies have focused on the examination of temporal correlation between resting state fMRI low-frequency oscillations (LFOs). Studies on the amplitudes of these low-frequency oscillations are rarely reported. Here, we used amplitude of low-frequency fluctuations (ALFF) and fractional ALFF (fALFF; the relative amplitude that resides in the low frequencies) to examine the amplitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

31
324
4
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 432 publications
(360 citation statements)
references
References 69 publications
31
324
4
1
Order By: Relevance
“…A large sample study from the multi-site fMRI Biomedical Informatics Network (FBIRN) (Turner et al, 2013) reported widespread regions of decreased fractional ALFF (fALFF) in schizophrenia, including posterior cortex. These results converge with reports of decreased fALFF in schizophrenia in posterior cortical regions including occipital and precuneus/posterior cingulate cortices (PCC) (Hoptman et al, 2010;Yu et al, 2014). There is, however, considerable variation in the regional pattern and direction of LFO amplitude alterations reported in schizophrenia, possibly owing to clinical and methodological differences among the small number of extant studies.…”
Section: Introductionsupporting
confidence: 86%
See 1 more Smart Citation
“…A large sample study from the multi-site fMRI Biomedical Informatics Network (FBIRN) (Turner et al, 2013) reported widespread regions of decreased fractional ALFF (fALFF) in schizophrenia, including posterior cortex. These results converge with reports of decreased fALFF in schizophrenia in posterior cortical regions including occipital and precuneus/posterior cingulate cortices (PCC) (Hoptman et al, 2010;Yu et al, 2014). There is, however, considerable variation in the regional pattern and direction of LFO amplitude alterations reported in schizophrenia, possibly owing to clinical and methodological differences among the small number of extant studies.…”
Section: Introductionsupporting
confidence: 86%
“…Measures of LFO amplitude have received relatively little attention in the schizophrenia literature, despite demonstration of regionally specific LFO differences between schizophrenia patients and healthy controls (He et al, 2013;Hoptman et al, 2010;Huang et al, 2010;Lui et al, 2010;Turner et al, 2013;Yu et al, 2013Yu et al, , 2014. A large sample study from the multi-site fMRI Biomedical Informatics Network (FBIRN) (Turner et al, 2013) reported widespread regions of decreased fractional ALFF (fALFF) in schizophrenia, including posterior cortex.…”
Section: Introductionmentioning
confidence: 99%
“…Depression is characterized by a decline of mood and activity and looks like the opposite of ADHD. Compared to normal controls, schizophrenia patients show decreased ALFF in the lingual gyrus [76] . Similar results are also seen in Schneiderian symptoms, and the severity of the symptoms is negatively correlated with rCBF in the left lingual gyrus in resting PET.…”
Section: Lingual Gyrusmentioning
confidence: 81%
“…A recent study using a multitaper spectral estimation found that the power spectral density of regional signals can identify changes in the oscillatory dynamics across conditions, and could characterize the nature and spatial extent of signal changes underlying changes in functional connectivity (Duff et al 2008). In disease condition, by measuring the ALFF and fALFF, Hoptman et al 2010 ave found reduced spontaneous neuronal activity in regions which show deficits in motor and low level sensory processing (the right precentral gyrus and lingular gyrus etc.) and show deficits in reward sensitivity (the right striatum), and increased activity in regions relevant to internally directed thought such as the medial frontal cortex and the hippocampus/ parahippocampus in schizophrenia.…”
Section: Properties Of Local Spontaneous Activitymentioning
confidence: 99%